Development of Identity Patterns of Bang Sadet Community, Ang Thong Province, Thailand - Chantanee, Metharat; Suksomwat, Patsawan (Area Based Development Research Journal, 2025)
Background: The Bang Sadet community, located in Pa Mok District, Ang Thong Province, central Thailand, is a historic settlement renowned for its cultural richness and long-standing traditions. Its distinctive cultural assets include the riverside landscape, the royal visit of Her Majesty Queen Sirikit, The Queen Mother, the historic Wat Tha Sutthawat temple, traditional raft houses, local folk singers, the majestic Yang Na (Dipterocarpus alatus) trees, ancient temple murals and Wang Palace doll center. Despite this abundance of tangible and intangible heritage, the community has struggled to effectively present these features as part of its tourism identity, resulting in low visitor numbers and limited local economic growth. Objectives and Methodology: This research aimed to develop and promote a distinctive tourism image for the Bang Sadet community through a participatory and systematic approach. The project consisted of five main stages: 1) Community awareness and collaboration: Building knowledge, understanding, and participation among local residents to enhance appreciation of cultural value and foster cooperation among community members, entrepreneurs, and relevant agencies; 2) Strategic analysis: Conducting a business environment analysis using SWOT and TOWS matrices to formulate context-appropriate development strategies; 3) Entrepreneurial capacity assessment: Evaluating the potential and readiness of local producers and service providers; 4) Identity creation: Designing and branding a unique community identity supported by storytelling; and 5) Promotion and dissemination: Publicizing the new image through media, products, and tourism events. Results and Findings: The participatory process generated tangible and measurable outcomes. A distinctive community identity pattern, inspired by local culture and history, was developed and applied to shirts, pants, and other fabric products. These identity-patterned items served as both tourism symbols and practical everyday attire. Community members and entrepreneurs began wearing them during welcoming ceremonies, tourism events, and official functions, while government agencies adopted the designs to help promote Bang Sadet at provincial and national levels. These initiatives transformed cultural identity into an economic asset. The sale of community-branded shirts generated additional household income, while new tourism-related occupations emerged, strengthening the local economy. Consistent branding enhanced visibility and recognition, positioning Bang Sadet as an attractive destination for domestic and international tourists. Beyond visual branding, the project fostered collaboration among nine local business groups, including artisans, textile producers, souvenir sellers, cultural performers, and small hospitality providers. Through cooperation, these groups shared experiences, coordinated marketing strategies, and organized community-based events offering immersive cultural experiences. The resulting network enabled more efficient resource use and long-term sustainability. The transmission of community identity extended beyond products. Entrepreneurs and partner organizations produced promotional media reflecting Bang Sadet’s culture and traditions, such as short documentaries, cultural exhibitions, and participation in regional fairs. These activities reinforced community pride and positioned local entrepreneurs as cultural ambassadors. Notable examples include online marketing through the community’s Facebook page and the collective wearing of identity-patterned shirts during community activities—strengthening both cohesion and visibility. The project’s impacts can be categorized into three major dimensions: policy, business, and academic. 1) Policy Impacts: The Bang Sadet model demonstrates an effective framework for developing community entrepreneurship and local branding through participatory processes. The collaboration between local residents, researchers, and government agencies can be replicated in other Thai communities to advance sustainable community-based tourism (CBT). Provincial and subdistrict administrative organizations, along with the Tourism Authority of Thailand (TAT), can adapt this model to design more inclusive and context-sensitive tourism programs. Moreover, the project supports Bang Sadet’s eligibility for official CBT certification, ensuring long-term recognition and sustainability at the policy level. 2) Business Impacts: The initiative strengthened local entrepreneurship and business innovation. Training sessions equipped participants with practical skills in interpretive communication, storytelling, tourism management, digital marketing, and product development. These competencies enhanced competitiveness and added value to local goods and services. By integrating storytelling with cultural design, Bang Sadet’s products gained distinctiveness and consumer appeal. The branding strategy fostered trust and recognition, reinforcing the community’s tourism image and stimulating spending on local products and services. The resulting economic activity improved income, employment, and living standards throughout the community. 3) Academic Impacts: From an academic standpoint, the research generated new insights into community-based tourism focused on cultural identity and entrepreneurship development. It demonstrated how collaborative partnerships between academics, researchers, and communities can produce co-created knowledge with tangible social benefits. The methodological framework—integrating participatory design, branding, and strategic business planning—provides a model adaptable to other cultural and tourism contexts. It can also be incorporated into university curricula on tourism management, community development, and heritage preservation, enriching both teaching and practice. Conclusions: The Bang Sadet project illustrates how a systematic and participatory approach to identity development can revitalize local tourism and stimulate economic, social, and cultural sustainability. By transforming traditional motifs and narratives into modern identity-based products, the community has created new avenues for self-representation, pride, and prosperity. The project underscores the power of community-led initiatives in ensuring that development is not externally imposed but grows organically from within. By bridging cultural heritage and modern innovation, Bang Sadet provides a replicable model for other communities seeking to achieve sustainable tourism and long-term resilience.